Multidimensional NMR methods for the solution state - Emsley, James W.; Morris, Gareth A. (Chichester, U. K. : Wiley, 2010)
Multidimensional NMR methods have transformed the way in which solution state NMR is used to elucidate the structures of chemical and biochemical systems
Includes bibliographical references and index
Keywords: Liquids -- Spectra; Nuclear magnetic resonance; Nuclear magnetic resonance spectroscopy